Two-phase flow behaviour and pattern in vertical pipes - Zubir, Mohamad Ardan; Zainon, Mohd Zamri (Asian Network for Scientific Information, 2011)
Two parts of research for two-phase flow study were highlighted which is flow behavior study and a void fraction measurement using Constant Electric Current Method (CECM). Both experiments are using a complete set of two-phase flow system that based on industrial scale. In flow pattern study, the investigation was focusing on the experimental work which based on systematic observation and measurements by using a high speed video camera and a few measurement equipments. Three different inner diameter pipes size of 21, 47 and 95 mm were used. The directions of flow were co-current upward flow and the flow velocity range is from 0.1 to 2.0 m sec-1. The effect of L/D and pipe size to the flow clearly describe from the graphs. To measure the void fraction using the Constant Electric Current Method (CECM) experiment, a same system in the flow pattern experiment was used, plus additional constant electric current supply system and data acquisitions system including Lab View software. A constant current power source supplied a DC electric power to a few kids of electrodes inside the pipes. One pair of electrode is used for supplying electric power and the others are for detecting the information of hold-up or film thickness. Data acquisition system recorded the voltage output and analyzing using the Lab View software. The value of void fraction and the type of flow pattern were predicted using this method. The results were compared to the predictions of void fraction from various void fraction models and correlations. © 2011 Asian Network for Scientific Information.